2023
DOI: 10.51586/2754-6209.2023.11.3.76.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contract Farming on Smallholder Farmers' Green Leaf Tea Production in Tanzania

Finias Dogeje,
Deus Ngaruko

Abstract: This paper investigates the impact of contract farming on green leaf tea output among Tanzanian smallholder farmers. Data from 393 growers from Mbeya and Njombe regions were collected in a cross-sectional survey and analysed descriptively using IBM Statistics Version 26. A multiple linear regression model was used to test the null hypothesis. The findings show that contract farming engagement (β=140.102; P=0.058) positively impact production. Moreover, household size (β=2.268; P=0.903) and gender (β=294.978; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Theoretically, contract farming as a form of vertical integrated is considered to be critical in addressing various challenges faced by farmers and processors as a result of different failures in spot markets (Dogeje& Ngaruko, 2023;Arouna et al, 2021;Ngaruko, 2012). This study hinges on the transaction cost theory to explain farmers' decision to participate in contract farming in the tea subsector.…”
Section: Literature Review Theoretical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, contract farming as a form of vertical integrated is considered to be critical in addressing various challenges faced by farmers and processors as a result of different failures in spot markets (Dogeje& Ngaruko, 2023;Arouna et al, 2021;Ngaruko, 2012). This study hinges on the transaction cost theory to explain farmers' decision to participate in contract farming in the tea subsector.…”
Section: Literature Review Theoretical Literature Reviewmentioning
confidence: 99%
“…Similarly, a study by Meemken and Bellemare (2019) in six developing countries (Bangladesh, Nigeria, Mozambique, Côte d'Ivoire, Uganda, and Tanzania) found that farmers engaged in contracting farming had higher income, precisely 10 percent more than those not engaged in this arrangement. Likewise, a study in Tanzania by Dogeje and Ngaruko (2023) revealed that contract farming positively influences Greenleaf tea production. These studies underscore that contract farming is critical to improved farmers' performance.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation